Enhancing Pre-School Students’ Vocabulary Skills through Digital Storytelling: A Classroom Action Research - Theodesia Lady Pratiwi; Yowina Trisannia; Leil Badrah Zaki (English Education:Journal of English Teaching and Research, 2025)
This classroom action research aimed to enhance preschool students’ vocabulary skills through the use of digital storytelling and to observe their engagement during the learning process. The study was conducted in two cycles, each consisted of two sessions with fourteen students aged five up to six years from a preschool class in Batam. Data was collected through pre and post-tests and classroom observations. Analysis involved comparing the mean test scores to assess vocabulary growth and using qualitative data from observations to evaluate the effectiveness of the digital storytelling actions within each cycle. The results demonstrated a significant improvement in students’ vocabulary mastery, evidenced by the average performance in the pre-test shifting to a very good category in the post-test. Furthermore, classroom observations confirmed higher levels of attention, enthusiasm, and interaction during the learning sessions. The findings confirm that digital storytelling is an effective and engaging method for vocabulary instruction in early childhood education. It supports vocabulary retention and student motivation even when applied with simple technology. This study recommends the integration of digital storytelling in early language learning and encourages future research to explore its long-term impact and application across various language skills.